2008
DOI: 10.1101/gad.504808
|View full text |Cite
|
Sign up to set email alerts
|

Against the oxidative damage theory of aging: superoxide dismutases protect against oxidative stress but have little or no effect on life span in Caenorhabditis elegans

Abstract: The superoxide radical (O 2 − ) has long been considered a major cause of aging. O 2 − in cytosolic, extracellular, and mitochondrial pools is detoxified by dedicated superoxide dismutase (SOD) isoforms. We tested the impact of each SOD isoform in Caenorhabditis elegans by manipulating its five sod genes and saw no major effects on life span. sod genes are not required for daf-2 insulin/ IGF-1 receptor mutant longevity. However, loss of the extracellular Cu/ZnSOD sod-4 enhances daf-2 longevity and constitutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
401
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 429 publications
(420 citation statements)
references
References 36 publications
16
401
1
2
Order By: Relevance
“…Superoxides are converted to hydrogen peroxide by superoxide dismutases (SOD) followed by a conversion to water by catalases (CTL) or peroxiredoxins (PRDX) (Sies, 2014). The C. elegans genome encodes 5 different superoxide dismutases ( sod‐1 to sod‐5 ), three different catalases ( ctl‐1 to ctl‐3 ), and three peroxiredoxins that are named according to their homology to the mammalian peroxiredoxins, prdx‐2 , prdx‐3, and prdx‐6 (Doonan et al ., 2008; Olahova et al ., 2008; Kumsta et al ., 2011). …”
Section: Resultsmentioning
confidence: 99%
“…Superoxides are converted to hydrogen peroxide by superoxide dismutases (SOD) followed by a conversion to water by catalases (CTL) or peroxiredoxins (PRDX) (Sies, 2014). The C. elegans genome encodes 5 different superoxide dismutases ( sod‐1 to sod‐5 ), three different catalases ( ctl‐1 to ctl‐3 ), and three peroxiredoxins that are named according to their homology to the mammalian peroxiredoxins, prdx‐2 , prdx‐3, and prdx‐6 (Doonan et al ., 2008; Olahova et al ., 2008; Kumsta et al ., 2011). …”
Section: Resultsmentioning
confidence: 99%
“…5a). Expression of sod‐1 and the genes encoding heat‐shock proteins is induced in the presence of oxidative stress (Park et al ., 2009), with SOD‐1 contributing to 80% of the total SOD activity in C. elegans (Doonan et al ., 2008). We observed that SOD activity was increased in LG2055‐fed worms compared with that in OP50‐fed worms (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In worms, insulin/IGF mutants have an increase in free-radical resistance (Gredilla et al 2001;Honda and Honda 1999). Although free radicals have been correlated with senescence, in both mice and worms, there is increasing evidence that they may not be the causative agent (Doonan et al 2008;Ran et al 2007;Van Raamsdonk and Hekimi 2009;Van Remmen et al 2003;Yen et al 2009). The target of rapamycin pathway, which may also link DR and insulin/IGF signaling, regulates autophagy, and this is important for both DR and insulin/IGF mediated longevity (Hansen et al 2008;Kaeberlein et al 2005;Kapahi et al 2004;Melendez et al 2003).…”
Section: Gompertz Analysismentioning
confidence: 99%